Plant Density and Regeneration in Relation to Anthropogenic Disturbance along Altitudinal and Horizontal Transect in the Sacred forest of Mata Vaishno Devi Hills (Trikuta Hills) of J.&K., India - Koul, A. R.; Chauhan, D. S.; Todaria, N. P. (Indian Forester, 2013)
The study related to density and regeneration in response to anthropogenic disturbance along the altitudinal and horizontal gradients in sacred forests of Trikuta hills in J&K showed a gradual decrease in anthropogenic disturbance level with the increase in altitudinal gradient and horizontal distance from the main track leading to shrine at each forest stand. On the basis of point scaling of different parameters, the higher altitudinal stand (2000-2200 m amsl) represented undisturbed stand, while intermediate (1400-1600 m asl) and lower altitudinal stands (800-1000 m amsl) were moderately disturbed. The density of tree species also showed an increasing trend with the increase in altitude 2 2 with highest density of 10.83 individuals/100m2 at stand III and lowest of 7.5 individuals /100m2 at stand I. In case of horizontal blocks for all the stands, density showedan increasing trend with the decreasing disturbance level. Seedling and sapling density at lower altitude indicate future generation of mixed species, intermediate stand revealed dominance of Pinus roxburghii, while at higher altitude Pinus roxburghii and Quercus leucotricophora have promising future.